Autophagy and pancreas disease - Vaccaro, Maria Ines (2008)
Autophagy is an evolutionarily preserved degradation process of cytoplasm cellular constituents, which has been known for its roles in protecting cells against stresses such as starvation and in eliminating defective cellular constituents including sub-cellular structures. It is essentially a form of self-cannibalism hence the name that means, “self-eating” in which the cell breaks down its own components. By mostly morphological studies, autophagy has been linked to a variety of pathological processes such as neurodegenerative diseases and tumorigenesis, which highlights its biological and medical importance. However, whether autophagy protects from or causes disease is unclear. Autophagic morphology was described in human pancreatitis by Helin H. et al in 1980. Actually, acute pancreatitis is one of the earlier pathological processes where autophagy has been described in a human tissue. Autophagy, autodigestion and cell death are early cellular events in acute pancreatitis. The aim of this review is to introduce a description of the autophagic process and to discuss the possible role of autophagy in acute pancreatitis.